2023
DOI: 10.2478/orga-2023-0007
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Constraints of Employee Satisfaction with Remote Work: An Empirical Analysis

Abstract: Background/Purpose The Covid 19 epidemic has forced many organizations to move to remote work (RW), and this trend is expected to continue even later in the post-epidemic period. Employees of the organization are at the heart of this transi-tion to RW, so identifying the factors that affect employee satisfaction with RW is very important for organizations to increase employee commitment and motivation. Therefore, the main objective of this study was to identify and prioritize the factors affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In addition to these key findings, it is essential to recognize that the COVID-19 pandemic served as a catalyst for redefining consumer behavior and business strategies globally. The pandemic prompted businesses to adapt rapidly to new circumstances, with many shifting their focus to e-commerce, contactless services, and remote work [63][64][65]. While air quality remains a critical factor, the pandemic demonstrated that external events could override its influence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these key findings, it is essential to recognize that the COVID-19 pandemic served as a catalyst for redefining consumer behavior and business strategies globally. The pandemic prompted businesses to adapt rapidly to new circumstances, with many shifting their focus to e-commerce, contactless services, and remote work [63][64][65]. While air quality remains a critical factor, the pandemic demonstrated that external events could override its influence.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, the effectiveness of the policy's execution can be seen in how satisfied the relocated persons are with the post-relocation assistance policy, which is a crucial factor in evaluating the effectiveness of the policy. Based on the framework construction for the satisfaction research of scholars [40,41], we constructed the satisfaction analysis framework of the post-relocation support policy of ex-suit poverty alleviation relocation.…”
Section: Analysis Framework Constructionmentioning
confidence: 99%
“…In the context of remote work, job satisfaction and employee performance are now factors that reduce work-family conflicts [99]. Furthermore, the job happiness of employees who work remotely is impacted by factors such as restricted communication, work-family balance, institutional and technological assistance, and job satisfaction [100]. Additionally, it has been observed that in a remote work setting, institutional and technical support affect work-life balance [101].…”
Section: Fssb Wfps and Job Satisfaction In Remote Workmentioning
confidence: 99%